Influence of pesticide effluent on Allium cepa L. (onion) plants - Mishra, Kumkum; Sanwal, Eera; Tandon, PK; Gupta, Kiran (International Journal of Environment, 2015)
An investigation was made to find out the effect of different doses (25, 50, 75 and 100%) of pesticide effluents (Indian Pesticide Ltd) on plant growth and certain metabolic parameters (height, total chlorophyll, carotenoid, protein and sugar contents, MDA content, catalase and peroxidase activity ) in Allium cepa L. plants. Plant growth in terms of its height, total chlorophyll, carotenoid, protein and sugar contents were found to be decreased at increasing doses of pesticide effluents. However, other activities of two antioxidative iron viz. catalase and peroxidase also the MDA (Malondialdehyde) content were found to be progressively stimulated at increasing doses of the effluent. DOI: http://dx.doi.org/10.3126/ije.v4i2.12629 International Journal of Environment Vol.4(2) 2015: 95-105